GLOBAL CONCENTRATION OF PULP EXPORTS - Coelho Junior, Luiz Moreira; Selvatti, Thaisa de Sousa; Alencar, Filipe Vanderlei; Santos Júnior, Edvaldo Pereira; Borges, Luís Antônio Coimbra; Rezende, José Luiz Pereira (Floresta, 2018)
This study analyzed the evolution and degree of the global concentration of pulp exports from 1961 to 2014. In order to measure and analyze the concentration, the following indicators were used: Concentration Ratio [CR(k)]; Herfindahl-Hirschman Index (HHI); Theil Entropy Index (E); Hall and Tideman Index (HTI); Comprehensive Concentration Index (CCI); and Gini Coefficient (G). We concluded that there was a tendency of growth in the global pulp exports during the analyzed period due to an increase in demand driven by population growth and to per capita consumption, enhancing the increase in the number of exporting countries. The CR(k) of the global pulp exporting countries showed that the four [CR(4)] and eight [CR(8)] largest countries present a high concentration, with an oligopolistic market structure and competitive advantage. About 100% of exports are dominated by the 20 largest countries [CR(20)]. The HHI, E, HTI, and CCI indicators showed that there is a concentration in global pulp exportation and presented a deconcentrating tendency. Despite the increase in the number of exporting countries, there was no significant reduction in the inequality of global pulp exports. According to the Gini Coefficient, the inequality was strong to absolute.